Modern approaches to the prevention and correction of complications caused by systemic treatment of severe acne forms - M. M. Tlish; M. E. Shavilova (State Scientific Center of Dermatovenereology and Cosmetology, 2019)
Background. According to European and RF clinical guidelines, only the systemic use of isotretinoin in severe acne has a high level of evidence. However, this therapy is frequently associated with the development of retinoid dermatitis, the prevention and correction of which requires the application of emollients. Aim. To evaluate the efficacy and tolerability of the Perfectoin cream during treatment and prevention of retinoid dermatitis in patients with severe acne receiving systemic treatment with isotretinoin.Materials and methods. Two groups of patients each comprising 38 people with moderate, severe and resistant to standard therapy forms of acne were observed. Each group included 22 patients with retinoic dermatitis manifestations and 16 without such symptoms. The patients in the main and comparison groups were prescribed the Perfectoin cream and the dexpanthenol cream, respectively. Control of the skin condition was performed prior to the study and following 1, 3 and 6 months of therapy. Assessment parameters were the main symptoms of retinoid dermatitis (erythema, lichenification, excoriation, itching, feeling of dryness/tightness of the skin), indicators of the hydration of the horny layer of the epidermis and the transepidermal loss of moisture, as well as the dermatology life quality index.Results. The study has shown that the Perfectoin cream in patients with acne receiving isotretinoin therapy helps to restore skin hydration and leads to a rapid regression of the main dermatological symptoms of retinoid dermatitis, thus improving the overall quality of patients' life.